Timing of activity in early visual cortex as revealed by transcranial magnetic stimulation. - Corthout, E; Uttl, B; Walsh, V; Hallett, M; Cowey, A (1999)
To determine the timing of visual processing in the early visual cortex, we applied single pulse transcranial magnetic stimulation to the occipital pole of healthy subjects while they were engaged in a forced-choice visual letter-identification task. We found two separate periods of activity, the first ranging from 20 to 60 ms after the onset of the visual stimulus, and the second ranging from 100 to 140 ms after the onset of the visual stimulus. We suggest that these two periods reflect necessary activity in V1, before and after re-entry.